Effectiveness of the e-Tabac Info Service application for smoking cessation: a pragmatic randomised controlled trial. Issue 10 (27th October 2020) - Affret, Aurélie; Luc, Amandine; Baumann, Cédric; Bergman, Pierre; Le Faou, Anne-Laurence; Pasquereau, Anne; Arwidson, Pierre; Alla, François; Cambon, Linda
Abstract : Objective: To compare the effectiveness of the mobile e-Tabac Info Service (e-TIS) application (app) for helping adult smokers quit smoking with current practices. Design: Pragmatic randomised controlled trial with a 1-year follow-up (2017–2018). Setting: France, population-wide level. Participants: 2806 adult smokers who wished to quit smoking were recruited via the website of the French National Mandatory Health Insurance fund. Of them, 1400 were randomised to the e-TIS app arm and 1406 were randomised to the current practices arm (control). Intervention: The app involved personalised interactive contacts that included questionnaires, advice, activities and text messages. All contacts were individually tailored and based on each smoker's progress. In the control group, recommended practices for quitting smoking were described on a non-interactive website. Primary and secondary outcomes measures: The primary outcome was 7-day point prevalence abstinence (PPA) at 6 months. The secondary outcomes included continuous abstinence rates at 6 and 12 months, minimum 24-hour point abstinence at 3 months, minimum 30-day point abstinence at 12 months and number and duration of quit attempts. Results: There was no difference between the e-TIS and control arms for the primary outcome (12.6% vs 13.7% for 7-day PPA at 6 months, p=0.3949, intention-to-treat analysis). However, e-TIS participants with high levels of exposure to the app, which was defined by the completion of at least eight activities or questionnaires, showed higher rates of smoking cessation than the control participants (17.6% vs 12.9% for 7-day PPA at 6 months, p=0.0169, per-protocol analysis). Conclusion: Use of the e-TIS app was not associated with a higher rate of smoking cessation. However, high level of exposure to the e-TIS app may have been more effective than current practices. Trial registration number: NCT02841683 .